Ticklish Questions: Pseudo-Proclus and Job of Edessa on the Workings of the Elemental Qualities - Hansberger, Rotraud (Oriens, 2014)
This article examines the Pseudo-Proclean text Questions on Natural Things (Masāʾil Frqlīs fī l-ašyāʾ aṭ-ṭabīʿiyya) in close comparison with its parallels in the second Mīmrā of Job of Edessa’s Book of Treasures. It tries to shed some light on the provenance and the sources of these texts, their place in the Problemata physica tradition, their relation to each other and to the Kitāb Sirr al-ḫalīqa, and the interests behind the compilation of the particular set of questions we encounter in them. Both texts are appended in the original Arabic and Syriac with facing English translations.